THE INFLUENCE OF DATA QUALITY ON INFORMATION SYSTEMS MANAGEMENT (MIS) WITH THE ACCURACY OF PHARMACY LOGISTICS PLANNING IN Prof. Dr. H. ALOEI SABOE REGIONAL HOSPITAL - Gumohung, Fatricia; Malaha, Adnan; Abbas, Syahrawanty S (Journal of Health, Technology and Science (JHTS), 2026)
This study aims to analyze the influence of data quality within the Management Information System (MIS) on the accuracy of pharmaceutical logistics planning at Prof. Dr. H. Aloei Saboe Regional Hospital. In the current era of healthcare digitalization, the precision of logistics planning is heavily dependent on the integrity of data generated by integrated systems. The research employed a quantitative approach with an explanatory design, collecting data through questionnaires distributed to respondents across planning, medical support, information technology, and pharmacy departments. Data were analyzed using univariate frequency distribution and bivariate Chi-Square statistical tests. The results indicate that the quality of data within the Hospital Management Information System (SIMRS) is predominantly perceived as good, which directly corresponds to a high level of accuracy in pharmaceutical logistics planning. The statistical analysis revealed a highly significant relationship between MIS data quality and planning accuracy, identifying data precision and real-time updates as the primary determinants of success. Consequently, the study concludes that superior data integrity within the system is essential for minimizing operational risks, such as medication stockouts and budgetary inefficiencies, thereby ensuring the reliability of regional healthcare delivery.